Description of the student’s academic performance in the English I course of the Bachelor in International Relations of the Schools of law at the University of El Salvador (Central campus), semester I-2019 - Cuadra Zelaya, Enyie Michelle; Maradiaga Velasco, Carlos Eduardo (2024)
Description of the students’ academic performance in the English I course of the Bachelor in International Relations of the Schools of Law at the University of El Salvador (Central campus), Semester I –2019.The English I program of the Bachelor in International Relations of the School of Law at the University of El Salvador stablishes that students are required to bring previous knowledge of the English language, and the main challenge that students face in this bachelor when taking this subject is that most of them do not have the English level required. This present proposal will characterize the strategies that students use to cope with the contents in the program, and also the methodology that teachers use during the class time to develop the contents of the English I program using a mixture of qualitative and quantitative approaches represented by the instruments such as observations, interviews, a questionnaire, and tests that were administered to students in the sample groups. Then these results were collected to be analyzed in an inductive way. Results are expected to show how students deal with the lack of the English level required and to diagnose which is the English level that they developed after having finished the course.